The Fatal error: [File:D:/build/++Portal/Sync/Engine/Source/Runtime/Core/Private/Internationalization/ICUInternationalization.cpp] [Line: 153] ICU data directory was not discovered: ../../../Engine/Programs/CrashReportClient/Content/Internationalization ../. - Siregar, Sri Hilma; Syahbella, Olif; Ramadhanti, Aulia Rizki (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
This research aims to determine the quality of bricks mixed with different variations of sawdust and three types of testing and two characterizations have been carried out. The process of making bricks with the addition of wood dust is carried out by mixing montmorillonite and wood powder until homogeneous, with a mixture percentage of wood powder and bentonite of 0% (as a control), 10%, 20%, 30% and 50%, then dried and burned. Then the bricks are tested for three parameters, namely compressive strength test, acoustic test and water absorption test. Based on the test results, each test parameter obtained was a minimum compressive strength value of 43.75 kg/cm2 and a maximum of 82.57 kg/cm2, where variations 1 and 2 met the quality requirements (according to class III category according to SNI 15-2094- 2000). The acoustic test results obtained the best results in all variations in the second and third tests at Ls (night level) and the water absorption value was obtained at a minimum of 11.16% and a maximum of 60.98%, where variation 1 meets the quality requirements (according to SNI 15 standards –2094–2000).